An indigenized framework for game design curriculum for African Universities - Randle, Oluwarotimi (Universitas Kanjuruhan Malang, 2024)
The aim of this paper is to reposition game design studies curriculum in Africa by modelling the African Ubuntu philosophy. This study utilized an inductive content analysis via transformative paradigm to identify relevant tenants that contribute to this conceptual paper. Furthermore, thematic approach was utilized to organize the are identified points int categories and subcategories. The utilization and introduction of the African ubuntu philosophy to game design curriculum follows 9 vital stages will be actualized. Researchers are motivated to conduct empirical and qualitative experiments on the African ubuntu philosophy for indigenized game curriculum. Utilizing indigenization as the game design curriculum will increase enrolment, programs easily accessible and help African content become global, as well as help African economies to grow. An indigenized policy will help many local talents and grow the south African economy.